Child Labor Efforts to Prevent Exploitation Child for Public Poor - Soetji Andari; Ikawati Ikawati; Istiana Hermawati; Akhmad Purnama; Murdiyanto Murdiyanto; Trigutomo Trigutomo; Sri Yuni Murti Widyawati (Program Studi DIII Rekam Medis dan Informasi Kesehatan, 2023)
Child labor is a term for employing children under 18 years of age. Child labor is the exploitation of a child for work usually on a low salary without other guarantees. The background of child labor due to poverty causes children to have to work to support their families. This research uses descriptive qualitative method, seeks to describe the causes of children working and the impact of children working. The research was carried out in Indramayu Regency, Sukabumi Regency, Ponorogo Regency, Malang Regency, Central Lombok Regency as the locations that contributed a lot of migrant workers abroad. The number of respondents was 150 children working in the informal sector, including migrant workers. The background of workers comes from poor families with low parental education levels. The findings of the cause of working children are parental poverty due to low parental education levels, lack of work skills, low income. The impact of working children experiencing exploitation includes 70% working more than 9 hours, getting wages but being cut without the child's knowledge, getting wages but not in accordance with the minimum wage standard, the promised work is not in accordance with reality (67%), loss of communication with parents 83%, and the occurrence of violence in the workplace such as discomfort, coercion, threats, prone to sexual harassment (50%). The impact of working children has a contribution to their family as much as 80%. Recommendations need to prevent the exploitation of child labor through empowering poor families in pockets of poverty. Preventive protection measures mean that the state, government, local governments, communities, families, and parents or guardians are fully responsible and obliged to implement child protection.